Association of oxidative balance score with hearing loss and tinnitus: NHANES 1999–2018 - Lai, Haohong; Yin, Jiyuan; Yang, Haidi (Frontiers in Nutrition, 2024)
Background: Oxidative stress is associated with the occurrence of hearing loss and tinnitus. The oxidative balance score (OBS), a composite indicator evaluating the balance between antioxidant and pro-oxidative components across various dietary and lifestyle factors, indicates the overall oxidative balance status. However, the association of OBS with hearing loss and tinnitus has not been reported previously. Methods: Cross-sectional data from the National Health and Nutrition Examination Survey (NHANES) 1999–2018 were analyzed. Weighted multivariable logistic regression, weighted multivariable linear regression, and restricted cubic spline curve (RCS) regression were employed to explore the relationship between OBS and hearing loss at speech, low, and high frequencies, along with tinnitus. Subgroup analysis and sensitivity analysis were used to ascertain the consistency across subgroups and stability of the results. Results: We included 13,715 and 21,644 individuals to investigate the association between OBS and hearing loss, as well as between OBS and tinnitus, respectively. The second, third, and fourth quartiles of OBS were significantly associated with a lower risk of hearing loss at speech, low, and high frequencies, as well as tinnitus, compared to the lowest quartile. The RCS regression analysis indicated a negative linear association of OBS with hearing loss and tinnitus. Most associations were maintained in subgroup analysis and sensitivity analysis. Additionally, the dietary and lifestyle OBS independently contribute to the protection against hearing loss and tinnitus. Conclusion: OBS is negatively correlated with the risk of hearing loss and tinnitus. The findings suggest that combined antioxidant diet and lifestyle hold promise as potential strategies for reducing the prevalence of hearing loss and tinnitus.